Autophagy in Bone Remodeling: A Regulator of Oxidative Stress - Zhu, Chenyu; Shen, Shiwei; Zhang, Shihua; Huang, Mei; Zhang, Lan; Chen, Xi (Frontiers in Endocrinology, 2022)
Bone homeostasis involves bone formation and bone resorption, which are processes that maintain skeletal health. Oxidative stress is an independent risk factor, causing the dysfunction of bone homeostasis including osteoblast-induced osteogenesis and osteoclast-induced osteoclastogenesis, thereby leading to bone-related diseases, especially osteoporosis. Autophagy is the main cellular stress response system for the limination of damaged organelles and proteins, and it plays a critical role in the differentiation, apoptosis, and survival of bone cells, including bone marrow stem cells (BMSCs), osteoblasts, osteoclasts, and osteocytes. High evels of reactive oxygen species (ROS) induced by oxidative stress induce autophagy to protect against cell damage or even apoptosis. Additionally, pathways such as ROS/FOXO3, ROS/AMPK, ROS/Akt/mTOR, and ROS/JNK/c-Jun are involved in the regulation of oxidative stress-induced autophagy in bone cells, including osteoblasts, osteocytes and osteoclasts. This review discusses how autophagy regulates bone formation and bone resorption following oxidative stress and summarizes the potential protective mechanisms exerted by autophagy, thereby providing new insights regarding bone remodeling and potential therapeutic targets for osteoporosis.